Antiproliferative Activity of 2,3-Disubstituted Indoles Toward Apoptosis-Resistant Cancers Cells - Magedov, Igor V. (2013)
Many types of cancer, including glioma, melanoma, NSCLC, among others, are resistant to apoptosis induction and poorly responsive to current therapies with propaptotic agents. We describe a series of 2,3-disubstituted indoles, which display cytostatic rather than cytotoxic effects in cancer cells, and serve as a new chemical scaffold to develop anticancer agents capable of combating apoptosis-resistant cancers associated with dismal prognoses.